2005
DOI: 10.1038/sj.cgt.7700828
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of protein tyrosine phosphatases: potential molecular targets for cancer therapy

Abstract: Promoter methylation-mediated silencing is a hallmark of many established tumor suppressor genes. This review focuses on the methylation and suppression of a receptor-type tyrosine phosphatase gene, PTPRO, in a variety of solid and liquid tumors. In addition, PTPRO exhibits many other characteristics of a bona fide tumor suppressor. Reactivation of genes silenced by methylation using inhibitors of DNA methyltransferases and histone deacetylases, and the potential application of PTPRO as a molecular target for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 67 publications
0
50
0
Order By: Relevance
“…Furthermore, the effect of PTPROt expression on the action of fludarabine also opens up a new avenue to explore combination therapy with epigenetic drugs, especially in resilient cases in which PTPROt is suppressed. It is interesting that most classical protein tyrosine phosphatases harbor a CpG island (31). Although methylation of only a few protein tyrosine phosphatases has been reported in human cancer (see refs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect of PTPROt expression on the action of fludarabine also opens up a new avenue to explore combination therapy with epigenetic drugs, especially in resilient cases in which PTPROt is suppressed. It is interesting that most classical protein tyrosine phosphatases harbor a CpG island (31). Although methylation of only a few protein tyrosine phosphatases has been reported in human cancer (see refs.…”
Section: Discussionmentioning
confidence: 99%
“…This critical function of PTPs is involved in numerous intracellular signaling events that serve various biological behaviors, such as cell proliferation, differentiation, apoptosis, and so forth. 3,4 Recently, an accumulation of evidence has enriched the understanding of cancer biology, and it has been observed that PTPRO exhibits important …”
mentioning
confidence: 99%
“…4 Gene expression of AXL has been correlated with DNA methylation levels in an Sp1/Sp3 transcription factor binding site in the promoter, suggesting DNA methylation plays a key role in determining gene function. 5,6 CpG methylation at this site has been reported to have high heritability. 7 Recent evidence also suggests AXL is an imprinted gene whose expression is maternally transmitted in some but not all individuals and dependent on DNA methylation in the locus.…”
mentioning
confidence: 99%